O‐Mannosylation precedes and potentially controls the N‐glycosylation of a yeast cell wall glycoprotein - Ecker, Margit; Strahl, Sabine (EMBO reports, 2003)
Secretory proteins in yeast are N‐ and O‐glycosylated while they enter the endoplasmic reticulum. N‐glycosylation is initiated by the oligosaccharyl transferase complex and O‐mannosylation is initiated by distinct O‐mannosyltransferase complexes of the protein mannosyl transferase Pmt1/Pmt2 and Pmt4 families. Using covalently linked cell‐wall protein 5 (Ccw5) as a model, we show that the Pmt4 and Pmt1/Pmt2 mannosyltransferases glycosylate different domains of the Ccw5 protein, thereby mannosylating several consecutive serine and threonine residues. In addition, it is shown that O‐mannosylation by Pmt4 prevents N‐glycosylation by blocking the hydroxy amino acid of the single N‐glycosylation site present in Ccw5. These data prove that the O‐ and N‐glycosylation machineries compete for Ccw5; therefore O‐mannosylation by Pmt4 precedes N‐glycosylation.